1992
DOI: 10.7326/0003-4819-116-8-609
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Fish Oil in Ulcerative Colitis

Abstract: Four months of diet supplementation with fish oil in patients with inflammatory bowel disease resulted in reductions in rectal dialysate leukotriene B4 levels, improvements in histologic findings, and weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0
13

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(155 citation statements)
references
References 24 publications
6
135
0
13
Order By: Relevance
“…Campos et al 21 observed less inflammatory alterations in the intestinal wall of the rats treated with lipid emulsions rich in omega-3 fatty acids and greater protection against the development of morphological lesions. Similarly, the preservation of the morphological structure with the use of omega-3 fatty acids was also demonstrated in experimental 22 and clinical studies 23 . It has been discovered that long-chain fatty acids appear to be more effective intestinal stimulators and significant trophic effects on small intestinal mucosa in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al 21 observed less inflammatory alterations in the intestinal wall of the rats treated with lipid emulsions rich in omega-3 fatty acids and greater protection against the development of morphological lesions. Similarly, the preservation of the morphological structure with the use of omega-3 fatty acids was also demonstrated in experimental 22 and clinical studies 23 . It has been discovered that long-chain fatty acids appear to be more effective intestinal stimulators and significant trophic effects on small intestinal mucosa in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Because n-3 PUFAs reduce tissue levels of the immunosuppressive agents arachidonic acid and prostaglandin E2, increased intake of n-3 PUFAs is hypothesised to enhance immune response. In fact, Pomposelli et al (1989) and Stenson et al (1992) have reported that dietary fats rich in n-3 or n-6 PUFAs, respectively, modulate inflammatory responses both in experimental animal models and in clinical trials. Diets enriched with n-3 PUFAs lead to reduced inflammatory reactions in experimental mice, with the significant development of different antibody types in response to antigenic stimulation in comparison to mice fed with an n-6 PUFA-enriched diet (Albers et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous researches have shown that antioxidants such as tocopherols and carotenoids can be transferred from the feed to the milk and thereby improve the oxidative stability of milk (Granelli et al, 1998). Omega 3 PUFA are considered as important modulators of immune reactions (Calder et al, 2002) as shown in experimental animal models (Pomposelli et al, 1989) and in clinical trials (Stenson et al, 1992). Mechanisms involved in the regulation of immune response may be related to PUFA influence on cellular communication and activation through the synthesis of prostaglandins, tumour necrosis factor-α, interferon-γ, and other factors such as nitric oxide (Calder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%